2009
DOI: 10.1002/jip.95
|View full text |Cite
|
Sign up to set email alerts
|

When should evidence be disclosed in an interview with a suspect? An experiment with mock‐suspects

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…For example, several studies have found an association between the revelation of evidence and the gaining of further information (Bull & Leahy-Harland, 2012;Nystedt, Nielsen, & Kleffner, 2011;van der Sleen, 2009), while other (experimental) studies have revealed that certain evidence disclosure strategies have contributed to the rigorous testing of given accounts by mock suspects, and, in turn, the detection of either lies or truth (Dando, Bull, Ormerod, & Sandham, in press;Granhag, Strömwall, Willén, & Hartwig 2012;Hartwig, Granhag, Strömwall, & Kronkvist 2006;Hartwig, Granhag, Strömwall, & Vrij, 2005;Sorochinski et al, 2014). Yet other studies have found that disclosing strong evidence is associated with suspects' confessions (Bull & Soukara, 2010;Cassell & Hayman, 1996;Gudjonsson & Petursson, 1991;Kebbell, Hurren, & Roberts, 2006;Moston, Stephenson, & Williamson, 1992;Sellers & Kebbell, 2009;Soukara et al, 2009;Walsh & Bull, 2012a). These studies have provided consistency when concluding how important evidence disclosure is; however, there is much less agreement between them as to what particular strategy is more effective than another.…”
Section: Evidence Disclosure In Interviews With Suspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, several studies have found an association between the revelation of evidence and the gaining of further information (Bull & Leahy-Harland, 2012;Nystedt, Nielsen, & Kleffner, 2011;van der Sleen, 2009), while other (experimental) studies have revealed that certain evidence disclosure strategies have contributed to the rigorous testing of given accounts by mock suspects, and, in turn, the detection of either lies or truth (Dando, Bull, Ormerod, & Sandham, in press;Granhag, Strömwall, Willén, & Hartwig 2012;Hartwig, Granhag, Strömwall, & Kronkvist 2006;Hartwig, Granhag, Strömwall, & Vrij, 2005;Sorochinski et al, 2014). Yet other studies have found that disclosing strong evidence is associated with suspects' confessions (Bull & Soukara, 2010;Cassell & Hayman, 1996;Gudjonsson & Petursson, 1991;Kebbell, Hurren, & Roberts, 2006;Moston, Stephenson, & Williamson, 1992;Sellers & Kebbell, 2009;Soukara et al, 2009;Walsh & Bull, 2012a). These studies have provided consistency when concluding how important evidence disclosure is; however, there is much less agreement between them as to what particular strategy is more effective than another.…”
Section: Evidence Disclosure In Interviews With Suspectsmentioning
confidence: 99%
“…In summary, 'early' disclosure is that revealed at the start of the interview, before questions have been put to the suspects (Moston et al, 1992;Sellers & Kebbell, 2009;Leo, 1996), whereas 'gradual' evidence disclosure involves an incremental approach of 'drip-feeding' evidence throughout the interview, while interviewers simultaneously attempt to gain an account from suspects (Granhag, Strömwall, Willén, & Hartwig, 2012). In contrast, 'late' disclosure involves eliciting the whole story from the suspect, dealing with all potential alibis and potential excuses, before presenting the evidence (see Hartwig et al, 2005;Sorochinski et al, 2014).…”
Section: Evidence Disclosure In Interviews With Suspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bull (2014) provides a more detailed explanation of each of these evidence disclosure mode (EDM) strategies. In brief 'early' refers to evidence being disclosed at the start of the interview, before questions have been put to the suspect (see Moston et al, 1992;Sellers & Kebbell, 2009;Leo, 1996). 'Gradual' evidence disclosure involves a phased presentation of information/evidence, provided in a 'drip-feed' effect throughout the interview (Dando & Bull, 2011;Granhag et al, 2012).…”
Section: Evidence Disclosure Strategiesmentioning
confidence: 99%
“…During the 1990s a model for the interviewing of suspects was implemented in England and Wales, called the PEACE framework (see Milne & Bull, 1999;Shepherd & Griffiths, 2013, for a comprehensive description). Since its introduction, there have been several studies examining real-life investigative interviews that have been conducted in those countries (e.g.…”
Section: Introductionmentioning
confidence: 99%